MEMS Intellect Multiprobes Contacting Devices for Electrical Checking-up of Multilayers Commutative Boards and BGA/CSP Electronic Components - Nevliudov, I. Sh.; Palagin, V. A.; Razumov-Frizjuk, E. A.; Zharikova, I. V. (KHARKOV NATIONAL UNIVERSITY OF RADIOELECTRONICS, 2012)
The aim of this paper is to introduce a new method of multilayer commutative boards (printed, thick or thin film) and BGA components testing. Four types of test fixtures for connecting some thousands test points on unit under test to automatic test equipment are presented. Probes in proposed MEMS devices fulfilled as ball grid arrays on flexible film with aluminum microwires. Such test fixtures give opportunity for self-monitoring contact of each probe to test point on board. The simplified devices can be used for BGA components testing before soldering in electronic modules.
Keywords: Multilayer commutative boards; BGA/CSP components; electrical testing; test fixture; multiprobes contacting device; MEMS